1970
DOI: 10.3329/bmj.v39i2.7029
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Academic Achievers and Under Achievers Regarding Educational Environment of Medical Colleges in Bangladesh

Abstract: Key words: perception; educational environment; academic achiever; academic under-achiever; medical collegeDOI: 10.3329/bmj.v39i2.7029Bangladesh Medical Journal 2010, 39(2) pp.2-10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…These findings are consistent with those of Nahar et al, who reported higher scores among high achievers compared to underachievers. 26 Moreover, our results are partially consistent with those of Mayya and Roff, who reported that higher achievers had better academic self-perceptions and SSP. 34 Thus, efforts should be directed to improving the perceptions of low achievers, which is evidently linked to their academic performances.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These findings are consistent with those of Nahar et al, who reported higher scores among high achievers compared to underachievers. 26 Moreover, our results are partially consistent with those of Mayya and Roff, who reported that higher achievers had better academic self-perceptions and SSP. 34 Thus, efforts should be directed to improving the perceptions of low achievers, which is evidently linked to their academic performances.…”
Section: Discussionsupporting
confidence: 90%
“…These two weaknesses, with similar scores, were reported in other studies where traditional curricula were delivered. 25 , 26 However, recently-structured curricula also suffer from a lack of emphasis on factual teaching, which might explain the poor perception of this item among students in the integrated curriculum in this study. 27 These findings require that more attention be paid to social accountability when designing curricula and endorsing community-based activities as integral components of an integrated system, besides periodic program monitoring and development.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations